Avaliação temporal da cobertura de vegetação nativa do município de Buri-SP para os anos de 2008 e 2018 e cenário futuro com as áreas de preservação permanentes restauradas - Pereira, Dheosmani Sandro Marmo dos Santos (Universidade Federal de São Carlos, 2023)
Agriculture and forestry are economic activities frequently found in the state of São Paulo. Consequently, there is concern about the areas occupied by these activities, since native vegetation cover areas are the most affected by conversion and consequent deforestation. Due to its location in a region with a strong agricultural and timber industry, the municipality of Buri is subject to the suppression of native vegetation, both in permitted areas and in illegal ones, such as permanent preservation areas (APPs). Multitemporal spatial analysis allows us to obtain an overview of the modifications that have occurred in recent years, identifying possible irregularities and their dimensions. This study aimed to analyze the land use transitions that occurred between 2008 and 2018 in the municipality through transition matrices, in addition to evaluation and comparison with a future scenario where all APPs are restored, considering landscape asymmetries of area analysis, nuclear area analysis, proximity index, and connectivity index, related to forest fragments of the proposed scenarios. The study was based on the use of landscape analysis tools in geographic information systems (GIS). The results showed favorable scenarios for the native vegetation cover of the municipality, with an 8.2% increase in its area in recent years, resulting from possible regeneration or reforestation projects during that period. There was also a considerable reduction in livestock areas (47.2%), but a significant increase in forestry (22.5%) and agriculture (55.5%) areas. In APPs, there was also an increase in native vegetation cover (9.3%), and a decrease in grazing (44.8%), conversions considered favorable from an environmental point of view. However, there was also an increase in forestry (47.6%) and agriculture (131.8%) uses, requiring greater attention from the public authorities and property owners to address irregularities. The future scenario obtained the best indices in all analyzed metrics, which was already expected since in such a scenario, all permanent preservation areas are restored. Comparing the 2008 and 2018 scenarios, the more recent one had an advantage in almost all aspects, favoring the maintenance of ecosystems and preservation of natural resources. However, even with such advantages, attention must be paid to the higher index of forest fragmentation found, which also demonstrates the need for an effort to achieve environmental adequacy of these properties.
Temporal evaluation of native vegetation coverage in the municipality of Buri-SP for the years 2008 and 2018 and future scenario with restored permanent preservation areas
Keywords: Áreas de preservação permanente; Uso do solo; Análise de área; Análise de área nuclear; Índice de proximidade; Índice de conectividade; Permanent preservation areras; Use of the soil; Area analysis; Nuclear area analysis; Proximity index; Connectivity index; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL